Dynamic cytokine profiles of bloodstream infection caused by Klebsiella pneumoniae in China - Wei Yu; Linyan Zeng; Xiang Lian; Lushun Jiang; Hao Xu; Wenhui Guo; Beiwen Zheng; Yonghong Xiao (BMC, 2024)
Abstract Objectives The aim of this work was to assess dynamic cytokine profiles associated with bloodstream infection (BSI) caused by Klebsiella pneumoniae (Kpn) and investigate the clinical features associated with mortality. Methods A total of 114 patients with positive BSI-Kpn and 12 sepsis individuals without blood positive bacteria culture were followed up. Cytokine profiles were analyzed by multiplex immunoassay on the first, third, seventh and fourteenth day after diagnosis. The test cytokines included arginase, interferon-gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), interleukin (IL)-1β, IL-4, IL-6, IL-10, IL-12 (p70), and IL-23. The minimum inhibitory concentration (MIC) of 24 antibiotics were tested for BSI-Kpn. Risk factors associated with the 30-day mortality and 120-day mortality were evaluated using logistic analyses and nomogram. Results There were 55 out of 114 patients with BSI-Kpn were included. All isolates showed high susceptibility rate to novel avibactam combinations. The level of arginase was the highest in carbapenem-resistant Kpn (CRKP) patients. The AUCs of arginase, TNF-α and IL-4 reached 0.726, 0.495, and 0.549, respectively, whereas the AUC for the combination of these three cytokines was 0.805. Notably, 120-day mortality in patients with CRKP was higher than carbapenem-sensitive K. pneumoniae (CSKP). Furthermore, the long-term and high levels of IL-6 and IL-10 were associated with death. Conclusions High expression of arginase is correlated with CRKP. In addition, BSI-CRKP could result in indolent clinic course but poor long-term prognosis. Continuous increase of IL-6 and IL-10 were associated with mortality.